Class II antigens on dendritic cells from the synovial fluids of patients with inflammatory arthritis. - Knight, S C (1989)
Dendritic cells were enriched from synovial fluids (SF) of patients with inflammatory arthritis and studied by immunogold labelling and electron microscopy for expression of histocompatability antigens of the HLA-D locus. Dendritic cells from SF were larger than most of these from peripheral blood with a more extensive Golgi region and more lysosomes and microfilaments. Class II histocompatability antigens HLA-DR, -DP, -DQ and that labelled by the antibody RFDI were abundant on the dendritic cells. The macrophages in the enriched cells showed labelling for DR but little labelling with the other antibodies. DR, DP and RFDI were often concentrated at areas of contact between dendritic and other cells (other dendritic cells, macrophages or lymphocytes). On incubating labelled cells at 37 degrees C for 30 min many macrophages lost their DR label but dendritic cells always retained some surface label. Some gold labelling DR and DP was found in characteristic channels between the veils and became internalized in membrane-bound structures. A small proportion of the RFDI label internalized in areas resembling coated pits. Less DQ label internalized and appeared on vesicles inside vacuoles. Material bound to different class II molecules may thus be internalized or processed differently by dendritic cells. The presence in inflammatory lesions of large activated dendritic cells with high expression of class II antigens suggests that these cells could be presenting antigen to lymphocytes within the joints.